The Innovation of the Queue Numbers Zoning Program at the Population and Civil Registration Office of Blitar Regency - Naibaho, Kanro Johannes; Kurniawan Subagja, Iwan; Hakim, Azis (Dinasti International Journal of Digital Business Management, 2025)
The Queue Numbers Zoning Program is an innovation of the administrative registration service of civil registry developed by the Population and Civil Registration Office of Blitar Regency to manage and regulate the people’s queue on the adminstrative registration process of the civil registry. The aims of this study are to describe and analyze the innovation of the Queue Numbers Zoning Program, the supporting and inhibiting factors that affects this program. The result of this research showed that the innovation of the Queue Numbers Zoning Program was created in order to overcome and eliminated the problems existed on the queuing process in the adminstrative registration process of the civil registry and provides the publics with an easier access to filed their registration at the administration service of the civil registry by dividing the queue into three zones. The procedure of administering this program begin with the people who needs the administration service from the Population and Civil Registration Office of Blitar Regency, have to come to their village office or sub-district office and filed for a registration to the admistration officers.